An outbreak of Japanese encephalitis after two decades in Odisha, India - Dwibedi, Bhagirathi (Indian J Med Res, 2015)
Sudden deaths in children due to acute encephalitis syndrome (AES) from a tribal dominated district of Malkangiri in Odisha, India, was reported during September-November, 2012. The investigation was carried out to search for the possible viral aetiology that caused this outbreak. Clinico-epidemiological survey and seromolecular investigation were carried out to confirm the viral aetiology. Two hundred seventy two suspected cases with 24 deaths were observed. The patients presented with low to moderate grade fever (87%), headache (43%), vomiting (27%), cold (18%), cough (17%), body ache (15%), joint pain (15%), rash (15%), abdomen pain (9%), lethargy (5%), altered sensorium (8%), convulsion (2%), diarrhoea (3%), and haematemesis (3%). Laboratory investigation showed Japanese encephalitis virus (JEV) IgM in 13.8 per cent (13/94) in blood samples and JEV RNA in one of two cerebrospinal fluid (CSF) samples. Paddy fields close to the houses, high pig to cattle ratio, high density (33 per man hour density) of Culex vishnui mosquitoes, low socio-economic status and low health awareness in the tribal population were observed. This report confirmed the outbreak of JEV infection in Odisha after two decades.